ANALISIS KUALITAS PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP MINAT BELI ULANG SMARTPHONE SAMSUNG GALAXY SERIES (Studi Kasus pada Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Stikubank Semarang - Ilham Syahbana, 10.05.51.0073; Basiya, Robertus (Students Journal of Economic and Management, 2014)
Re buying interest is a psychological aspect which has considerable influence on the attitudes and behavior of interest is also a source of motivation that will drive someone to do what they do. Factors affecting the buying interest re-include: product quality, brand image, and price perception. The purpose of this study was to analyze the effect of product quality, brand image, and perception of the price of buying interest re-smartphone Samsung Galaxy Series. The population in this study is the students of the Faculty of Economics, University of Semarang Stikubank the re-purchase the smartphone Samsung Galaxy Series . The sample size used is based on the formula proposed by Taro obtained as many as 100 people . Purposive sampling technique sampling is a sampling technique to the data source specific considerations . Consideration of the samples in this study is that consumers who buy and use smartphones the Samsung Galaxy Series at least one month . Accidental sampling is taking respondents in the sample by coincidence met at the Faculty of Economics, University of Stikubank SemarangJenis data used in this study is primary data is data in the form of a questionnaire . The analytical tool used is multiple linear regression analysis . The results of the analysis can be concluded that : ( a) product quality has a positive effect on buying interest re- smartphone Samsung Galaxy Series . ( b ) brand image has a positive effect to enthusiasm buy to repeat smartphone Samsung Galaxy Series . (c) Perceived price has a positive effect to enthusiasm buy to repeat smartphone Samsung Galaxy Series .Keywords : product quality , brand image , price perceptions and Enthusiasm buy to repeat